A two-dimensional Reynolds averaged Navier–Stokes investigation on gap resonance and wave elevation around two side-by-side bodies with motions - Jiang, Zongyu; Tavakoli, Sasan; Kujala, Pentti; Hirdaris, Spyros (Physics of fluids (1994), 2023)
The coupled dynamics of wave elevation and motions around bodies floating in proximity may be sensitive to radiation and diffraction effects. In this paper, the influence of radiation on wave elevation is examined for two side-by-side boxes subject to forced sway, heave, and roll oscillations in a two-dimensional numerical wave tank. The effects of diffraction on wave elevation and the joint influence of radiation and diffraction are investigated in regular waves assuming free heave motions. Heaving of one or two boxes and single-box sway or roll excites a piston mode of water motions in the proximity gap. Synchronous sway or roll induces sloshing. The close relationship between gap resonance and rapid water exchange in and out of the gap is confirmed. Vortices within the gap drive water exchange and influence the gap wave elevation. Their impact is determined by both spatial and temporal distributions.